Desarrollo Social del Talento Humano de Enfermería del área de Gineco-Obstetricia del Hospital León Becerra de Milagro y su incidencia en el control de la Transmisión Vertical del VIH-SIDA (madre e hijo) del cantón Milagro. - Anguisaca Angulo, Nube Lilia (2014)
The present investigation was aimed, investigating ways to diagnosis of situation on the knowledge, skills and expertise of nurses in the area of Gynecology and Obstetrics Hospital of León Becerra Miracle on vertical HIV transmission AIDS (Mother-Child). The scientific methodology is descriptive. The scientist that allows conceptualization through strategically locates the objectives, goals and values to establish the cause and impact of research in this paper. The field research for which use the technique, survey and instrument, the structured questionnaire and led to a statistically representative sample of 9 people Lcdas and nursing , which make up the area of Obstetrics Gynecology. With these results, we proceeded to produce charts and graphs. Which states that the evidence existing scenario For more training and education dissemination was to provide users the vertical transmission rate is rising because there is still adherence by the human being, not only at national level if not at the global level if the statistics show. The conclusions and recommendations defined a proposed schedule of continuous training as the nursing staff have the tough task of working for the good of patients in conjunction with governmental organizations, also seeks to provide timely quality care. Warmth and humanity.